(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rambe IF, Rambey R, Siregar S. 2021. Species diversity, abundance, and wildlife conservation status in Batang Gadis National Park, North Sumatra, Indonesia. Biodiversitas 22: 5189-5196. Indonesia is one of the countries with the highest biodiversity in the world. Furthermore, the biodiversity of floral and faunal species is still being monitored and maintained, one of which is in the forest of the National Park. Batang Gadis National Park is a habitat for various species of endemic Sumatran wildlife, most of which are endangered species in the world. Therefore, this study aimed to inventory wild animals and to calculate their abundance in the Batang Gadis National Park. The study used camera traps as recording devices that were installed on permanent and non-permanent plots based on evidential animal trajectories in the National Park Management Section Region III Resort 7 Forest of Ampung Padang Forest in 2018. In the permanent plot, 10 species were documented within nine families, namely the Felidae, Tapiridae, Cervidae, Viverridae, Ursidae, Tragulidae, Suidae, Tupaiidae, and the Cercopithecidae. The highest species abundance was Macaca nemestrina (36.17%), and the second-highest was Muntiacus muntjak Zimmermann (14.89%), and then Tapirus indicus Desmarest (10,64%). Also, the Sumatran tiger (Panthera tigris sumatrae Pocock) was in the fourth position with a value of 10.63% of species abundance. Meanwhile, the lowest abundance index value was from clouded leopard (Neofelis diardi Cuvier) with 2.12%. The abundance of species from the non-permanent plots using camera trap documented a total of 13 species with 12 families namely Felidae, Tapiridae, Cervidae, Hystricidae, Viverridae, Muridae, Phasianidae, Tragulidae, Suidae, Muscicapidae, Tupaiidae, and Cercopithecidae. The highest was documented from wild boar (Sus scrofa Linnaeus) at 42.48% and the second-highest species abundance was macaque (N. nemestrina) at 26.144%. The lowest species abundance index values were tapir (T. indicus) and Javan blue robin (Myiomela diana Lesson) with 0,33% and 0,33 %, respectively. The existence of documented wildlife species in our study affirmsed the importance of Batang Gadis National Park as a natural habitat for some key and protected species.